Adaptive ATP-induced molecular condensation in membranized protocells - Vincent Mukwaya; Xiaolei Yu; Shuo Yang; Stephen Mann; Hongjing Dou (Proceedings of the National Academy of Sciences, 2025)
Liquid–liquid phase separation (LLPS) has been achieved in various cytomimetic (protocell) models, but controlling molecular condensation using noninert crowders to systematically alter protocell function remains challenging. Intracellular ATP levels influence protein–protein interactions, and dysregulation of ATP can alter cellular crowding dynamics, thereby disrupting the normal formation or dissolution of condensates. Here, we develop a membranized protocell model capable of endogenous LLPS and liquid–gel-like phase separation through precise manipulation of intermolecular interactions within semipermeable polysaccharide-based microcapsules (polysaccharidosomes, P-somes), prepared using microtemplate-guided assembly. We demonstrate that intraprotocellular diffusion-mediated LLPS can be extended into the liquid–gel-like domain by the uptake of the biologically active crowder ATP, resulting in a range of modalities dependent on the fine-tuning of molecular condensation. Endogenous enzyme activity in these crowded polysaccharidosomes is enhanced compared to free enzymes in solution, though this enhancement diminishes at higher levels of intraprotocellular condensation. Additionally, increased molecular crowding inhibits intraprotocell DNA strand displacement reactions. Our findings introduce an expedient and optimized approach to the batch construction of membranized protocell models with controllable molecular crowding and functional diversity. Our mix–incubate–wash protocol for inducing endogenous LLPS in membranized protocells offers potential applications in microreactor technology, environmental sensing, and the delivery and sustained release of therapeutics.